Temperature affects the sorption of trace metals by macro- and microplastics within marine intertidal sediments: insights from a long-term laboratory-based study - Tamara N. Kazmiruk; Juan José Alava; Juan José Alava; Eirikur Palsson; Leah I. Bendell (Frontiers in Marine Science)
Macro- and microplastics and trace metals are significant pollutants in the marine environment and have been reported in all ecosystems around the world. The process of sorption/desorption of trace metals by macro- and microplastics is influenced by various factors, including the morphological characteristics of macro- and microplastics, their adsorption capacity, and environmental conditions. This research provides and discusses laboratory experimental findings on the sorption of trace metals cadmium (Cd), copper (Cu), lead (Pb), and zinc (Zn) by macro- and microplastics of polyethylene terephthalate (PETE) and high-density polyethylene (HDPE) within two contrasting marine intertidal sedimentary environments with high and low organic matter content under conditions of constant temperatures (T=- 4.0°C, T=+ 4.0°C, and T=+18.0°C). Our aim is to determine the effect of temperature on trace metal sorption onto macro- and microplastics. Temperature alters the metals’ sorption by plastic by altering the rate of reaching equilibrium and equilibrium concentration, whereas constant temperature had only a minor influence on the partitioning of trace metals. Sediment organic matter influences sorption dynamics at all three temperatures T=- 4.0°C, T=+ 4.0°C, and T=+18.0°C. This study enhances our understanding of how temperature can effect trace metals-plastic particle interactions in the marine intertidal sedimentary environment providing insight as to conditions that will create the greatest threat to higher trophic levels by providing an additional vector of Cd, Cu, Pb, and Zn exposure into benthic food webs.